Periparturient changes in intake, rumen capacity, and selected blood metabolites in beef cows - Stanley, T.A.; Cochran, R.C.; Harmon, D.L.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four, ruminally cannulated, Hereford × Angus cows were used to study factors associated with feed intake patterns around parturition. Feed intake during the final trimester of gestation was relatively stable, in spite of a noticeable decrease in ruminal capacity. Postpartum feed intake appeared to increase, as did ruminal capacity. Blood progesterone fell after parturition, whereas estradiol did not change except for a large rise around parturition. Some plasma metabolites measured differed before and after calving; however, magnitude and patterns of change do not suggest a direct relationship with intake.
Keywords: Beef; Feed intake; Ruminal capacity; Gestation